Differences in the Accuracy of Age Estimation in Children Using the London Atlas and the Atlas of Dental Development in the Indonesian Population at RSGMP Nala Husada - Shintya Rizki Ayu Agitha; Icha Artyas Annariswati; Eddy Hermanto (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Teeth can be used for age estimation of the victim. Several atlases can be used to estimate age through teeth, such as the London Atlas(AL) and The Atlas of Dental Development in the Indonesian Population(ADDIP). The Atlas of Dental Development in the Indonesian Population (ADDIP) is a modification of the London atlas (AL), made by looking at the process of dental development of children in Indonesia from the age of 5 years to 23 years. Therefore, this study aims to compare the accuracy of child age estimation using the London Atlas (AL) and the Atlas of Dental Development in the Indonesian Population (ADDIP). Material and Methods: This study used 128 panoramic radiographs from pediatric patients aged 5 years to 16 years at RSGMP Nala Husada Surabaya from February to May 2025. Data analysis was conducted using SPSS software for different tests, including a Wilcoxon test. Results and Discussions: Using the London Atlas (AL) method, the average difference between chronological age and dental age was found to be between -0.13 and -1.51 years. Meanwhile, according to ADDIP, the average difference between chronological age and dental age was found to be between -0.03 and -1.31 years. Conclusion: ADDIP shows a smaller difference between chronological age and dental age than the AL, suggesting that ADDIP demonstrated higher accuracy than AL for estimating age in Indonesian children.